DEMAND ATTRIBUTES FOR SOCIAL HOUSING: EVIDENCE FROM HOUSING POLICY SCHEMES IN MALTA - Falzon, Joseph; Bezzina, Frank (European Scientific Journal, ESJ, 2013)
The paper focuses on the key attributes that underpin demand for social housing in Malta (an EU member state) during the 2000s and the extent to which the demand for social housing is addressed by the stock of units that were offered for sale by the Maltese Housing Authority. The analysis carried out focuses on the eight sales issues that were launched by the Housing Authority between October 2002 and November 2008. The paper presents nine stylized facts that underpin underlying demand. In this regard, key attributes of demand include the fact that the group of individuals eligible to apply for units from the housing authority has been implicitly increasing steadily during the period under review. Furthermore, the major part of applicants across the different categories seem to prefer larger three-bedroom apartments even though smaller units may be adequate given the number of children and the number of persons in the household. Another key stylized fact pertains to the fact that although the volume of applicants is quite large giving rise to excess demand, paradoxically a sizeable stock of units ends up unsold. The implications of the findings are discussed. The study goes on to provides recommendations and suggestions for further research that could better guide future buyers, as well as Maltese housing policy makers in their quest to offer affordable quality housing for persons with low income, persons with disabilities, and for vulnerable persons with social and housing difficulties.